Preserving Cultural Words: Direct Translation Applied in Relay Translation of Folklore - Rahmani, Irfa Luthfia; Syafaat, Pangeran Muhammad Faqih (IKIP Siliwangi, 2026)
Translating cultural word has become the phenomenal issues in translation. Many researches have focused on finding the accurate strategy to translate it. This study discussed the specific strategy that the translator can use to preserve the cultural words in the translation text especially in relay translation. It aims to see the ideological aspect in translation that is essential for evaluating discrepancies in cultural contexts. The descriptive qualitative research is employed on this research to analyze the cultural words and direct translation technique in the Anthology of Batu Bara Folklore. It consists three languages such as Malay, Bahasa Indonesia, and English that was translated using relay translation technique. The results showed that there are 108 cultural words found in the data. It is divided into 52 data (48%) of material culture, 30 data (28%) of social organization, 18 data (17%) of ecology, 4 data (4%) of social culture and gestures habits. Moreover, there are 98 data that use direct translation in the translation from Malay into Bahasa Indonesia and 88 data that use the same technique in Bahasa Indonesia into English text. It can be concluded there are more than 80% data that the meaning is being preserved by the translator.